Religious and Spiritual Values In Kalidasa’s Shakuntala - Yousuf, Ghulam-Sarwar (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The origins of Asian as well as Western drama and theatre are almost invariably connected with the gods or invisible forces. Pre-modern theatre forms are also usually linked with shamanism, healing processes, and the trance as well as with other ritual activities. For instance, the connection between Dionysius, the ancient fertility god, and Greek classical theatre is generally acknowledge. In the same way several examples may be cited from various Asian cultures and communities: the Chinese opera, the Japanese Noh theatre as well as several examples of traditional theatre in Southeast Asia which contain elements of ritual. The folk and classical traditions of Indian theatre demonstrate the same pattern.